DETERMINATION ATTITUDE TOWARD USING AND PURCHASE INTENTIONS: ANALYSIS OF PERCEIVED EASE OF USE AND PERCEIVED USEFULNESS (CASE STUDY OF INSTAGRAM SHOP’S FEATURES ON SOCIAL MEDIA INSTAGRAM) - Fatmawati M, Inayatullah; Ali, Hapzi (Dinasti International Journal of Management Science, 2021)
This study aims to analyze the effect of perceived ease of use and perceived usefulness on attitude toward using and the effect of perceived ease of use and perceived usefulness on purchase intentions and the effect of perceived ease of use and perceived usefulness on purchase intentions through attitude toward using. The population in this study are internet users who have done online shopping but have never made an online purchase transaction on Instagram and are domiciled in the Jakarta area. The number of samples used is based on the number of indicators at an error rate of 5%, which is 150. The survey was conducted using a questionnaire and then analyzed the data using Partial Least Square (PLS). The results showed that perceived ease of use had a positive and significant effect on attitude toward using, perceived usefulness had a positive and significant effect on attitude toward using, perceived ease of use had a positive and significant effect on purchase intentions, perceived usefulness had a positive and significant effect on purchase intention, attitude toward using had a positive and significant effect on purchase intentions and attitude toward using fully mediating between perceived of ease use and partially mediating between perceived usefulness on purchase intentions the Instagram Shop’s features on Social Media Instagram.